A implementação do “Novo” Ensino Médio no município de Terra Roxa: texto e contextos - Kozakowski, Sandra Mara de Moraes (2022)
The implementation of educational policies, contemplating the specifics of the education for Middle School and Professional School during the government of Michael Temer were established in 2016 by the Provisory Measure number 746, which originated Law number 13.415 from February 16th, 2017. With the Reformation, the last stage of Brazilian Basic Education receives the adjective “New” thus, starting to be named “New” Middle School. The proposal for change considers the (re) elaboration of curricular from the Common National Curriculum Base. The choice by focused in technical and formatting knowledge as well as in the distribution of Work Load of high school. In face of this conjuncture, this research, which has as study object the “New” Middle School has this problem: “The Law 13.415/2017 may be a strategy of merchandizing and disqualification of Middle School, in consonance with the capitalist regime?” The general objective of this study is to investigate the organization and implementation of the “New” Average teaching in face of the proposal of the curricular organization in full time and the amplification of work load the Formatting Itineraries. The research covers schools from the State Network of education pertaining to the city of “Terra Roxa, Paraná”. For the construction of the research, a qualitative approach was chosen with documentary and bibliographic research through the method of historical-dialectical materialism. The research is based on primary sources: Normative Documents that regulate the proposal of the “New” High School in the Federal, State and Local scope and on secondary sources: bibliographic references of national and international authors that deal with education in general and high school and education professional specifically. The presentation of the study is organized chapters. The first is the introduction which points out the intention and the elements that will guide the course of the research; the second chapter, taking as a cut the years from 1960 to 2020, presents a set of facts that are part of the historical trajectory of Brazilian secondary education and professional education. The third chapter presents the path taken in the implementation phase of the “New” High School, highlighting the main changes that have taken place since Law nº 13.415/2017. The fourth chapter exposes, in a critical and reflective way, the consequences of the implementation of the “New” High School in the State Network schools belonging to the municipality of Terra Roxa - Paraná. Finally, the conclusion is presented, drawn from the studies presented in the previous chapters to answer the problem and the investigative questions of this research. It is concluded that although the reform is in its implementation time, it is possible to verify that the changes to high school and professional education are determined according to the requirements of capitalism. The evidence points to the fact that the process of commodification of education is linked to the expansion of privatization. The reform allows for ratification and publicity that, in line with the capitalist regime, disqualifies secondary education and professional training